The Effect of Successful Branding on Consumer Behavior and Loyalty - HAJJI, CHAIMA EL (İstanbul Kültür Üniversitesi, 2023)
The study explores the relationship between successful branding and consumer behavior and customer loyalty. Branding is essential in today's rapidly evolving marketplace, affecting customer behavior and purchasing decisions. This research interprets the factors influencing consumer behavior and purchasing decisions and their association with successful branding. The approach utilizes a quantitative research method. The sample comprises 250 respondents, with a comprehensive questionnaire as the data collection tool. SPSS software (IBM SPSS Statistics 28) quantifies the data using frequency, reliability, EFA validity, t-test, correlation, and regression. The study reveals a positive relationship between successful branding, consumer behavior, and customer loyalty. This finding is beneficial for marketing professionals to understand branding's significance, allowing them to make informed decisions about brand management, marketing campaigns, and customer engagement methods. The research aids practitioners to enhance branding efforts and foster long-term customer relationships. Effective branding is crucial for influencing consumer behavior and encouraging client loyalty. The relationship between branding and customer outcomes is explored using quantitative techniques and SPSS software analysis. The study offers marketers information to improve brand management strategies and nurture enduring client relationships.

Bu çalışma, başarılı markalaşma ile tüketici davranışı ve müşteri sadakati arasındaki ilişkiyi inceler. Markalaşmanın müşteri davranışını etkilemesi ve günümüz pazarında hayati önem taşıması üzerine odaklanır. Tüketici davranışını ve satın alma kararlarını etkileyen faktörlerin markalaşma ile ilişkisi yorumlanır. Çalışma, nicel bir araştırma yöntemi ve kapsamlı bir anket kullanır. 250 yanıtlayıcıdan oluşan örneklem kullanılmıştır. IBM SPSS Statistics 28 ile veriler analiz edilmiştir. Çalışma, başarılı markalaşma, tüketici davranışı ve müşteri sadakati arasında pozitif bir ilişki olduğunu gösterir. Pazarlama profesyonelleri için markalaşmanın önemini anlamada yardımcıdır. Araştırma, uygulayıcılara markalaşma çabalarını geliştirme ve uzun vadeli müşteri ilişkilerini teşvik etme konusunda destek sağlar. Etkili markalaşmanın tüketici davranışını etkileme ve müşteri sadakatini teşvik etme üzerindeki etkisi tartışılır. Markalaşma ve müşteri sonuçları arasındaki ilişki, nicel teknikler kullanılarak analiz edilir. Çalışma, pazarlamacılara marka yönetimi stratejilerini geliştirme ve müşteri ilişkilerini sürdürme konusunda bilgi sunar.
Başarılı Marka Oluşumunun Tüketici Davranışı ve Bağlılık Üzerindeki Etkisi
▪ Yüksek lisans tezi.
Keywords: Successful Branding; Consumer Behavior; Customer Loyalty; Factors Influencing Consumer Behavior; Brand Management